ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR DAGING SAPI DI INDONESIA TAHUN 1996 s.d 2017 - RAMADHAN RAMADHAN; ALI WARDHANA (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Ramadan (2019). Analysis of factor-factor that affect the import of beef in Indonesia year 1996 to 2017. Advisor : Ali Wardhana, SP, M.Si.            This study aims to determine how the effect of import prices, exchange rates, and GDP per.capita of the number of imports of beef in the country of Indonesia during 1996 to 2017. The data used are time series data.            The analytical method used is multiple regression analysis with estimation using E-views 9.The analysis showed thatimport prices has negative and notsignificant to the number of imports of beef in the countryof Indonesia, the exchange rate has a positive effect and no significant effect on the number of imports of beef in the country of Indonesia, and GDP per.capita positive and significant impact on the number of imports of beef in the country of.Indonesia year 1996 to 2017.        Keywords : Import, Import Prices, Exchange Rate, and GDP per capita